Models of administrative and legal regulation of sponsorship and patronage in the EU - Антошина, Ірина Володимирівна; Антошина, І. В.; Антошина, Ирина Владимировна; Antoshyna, Iryna V.; Бондаренко, Аліна Ігорівна; Бондаренко, А. І.; Бондаренко, Алина Игоревна; Bondarenko, Alina І. (Baltija Publishing, 2019)
Today, patronage is the key source of non-governmental support of the socio-cultural advancement of the state because, as the world’s practice shows, the state funding is often not enough for conserving and developing the national and cultural heritage. Across the world and Europe, increasing attention is paid to the traditions of charity, corporate philanthropy is in progress, and business ethics are growing. In developed countries, the pursuit of charity activity is caused by a high level of social responsibility of business entities. Both large corporations and wealthy people establish charitable funds or provide a good deal of money for relevant purposes. The problems of patronage or sponsorship as means for guaranteeing the realization of socio-cultural programmes, research initiatives and continual activity of not-for-profit organizations are topical and need an extension study in terms of conditions and prospects for the development. The purpose of the article is the analysis of the experience of administrative regulation of patronage and sponsorship in different countries and its growth potential in Ukraine in the context of international integration and scientific and technological progress. The situation is complicated by the fact that this regulatory scope has originated more recently in the world’s practice, and many problems remain unsettled. For example, let’s consider some forms of financial rewards used in the rest of the world. In the developed countries, there are models of cooperation with a private fund in the social, cultural, academic and other spheres of social life. They are as follows: the state as a leader; private fund as a leader; partnership and functional division of labour between the state and capital. In social practices, they usually co-exist with a dominant one of them. The first model prevails in France and Italy, the second – in the USA, the third – in the Federal Republic of Germany. Recently, there has been a gradual transition to the third model, which will become dominant in Western countries. Compared to Western Europe, there has been no moral rehabilitation of wealth in Ukraine, which has affected the motivation of charity. It is noteworthy that in the last decade, especially in European countries, state and state-social funds, which are financed using budget funds and the contributions of patrons, have been created. In general, analyzing various forms of patronage and sponsorship in the field of culture of the countries of the European region, it can be argued that in modern Western countries there is a sweeping trend to decrease direct state support of culture by indirect. The attraction of funds of entrepreneurs and non-governmental organizations in various forms is purposefully stimulated by state cultural policy, laws on patronage. In Ukraine, state intervention in the charity area is minimal. It is limited to the statutory regulation of charity activity, registration and accounting of charity organizations. At the same time, some specific normalization of patronage and sponsorship is next to none because it is distinguished among other charity activities mostly by patrons, sponsors, and mass media.

Сьогодні меценатство є основним джерелом недержавної підтримки соціально-культурного розвитку держави, оскільки, як показує світова практика, державного фінансування часто недостатньо для збереження та розвитку національно-культурної спадщини. У світі та Європі все більше уваги приділяється традиціям благодійності, розвивається корпоративна філантропія, зростає бізнес-етика. У розвинених країнах заняття благодійною діяльністю зумовлене високим рівнем соціальної відповідальності суб’єктів господарювання. І великі корпорації, і заможні люди створюють благодійні фонди або виділяють чималі гроші на відповідні цілі. Проблеми меценатства чи спонсорства як засобів забезпечення реалізації соціально-культурних програм, дослідницьких ініціатив та постійної діяльності некомерційних організацій є актуальними та потребують розширеного вивчення з точки зору умов та перспектив розвитку. Метою статті є аналіз досвіду адміністративного регулювання меценатської та спонсорської діяльності в різних країнах та її потенціалу зростання в Україні в умовах міжнародної інтеграції та науково-технічного прогресу. Ситуація ускладнюється тим, що ця сфера регулювання у світовій практиці виникла зовсім недавно, і багато проблем залишаються невирішеними. Наприклад, давайте розглянемо деякі форми фінансової винагороди, які використовуються в решті світу. У розвинених країнах існують моделі співпраці з приватним фондом у соціальній, культурній, академічній та інших сферах суспільного життя. Вони такі: держава як лідер; приватний фонд як лідер; партнерство і функціональний поділ праці між державою і капіталом. У соціальних практиках вони зазвичай співіснують з домінуючим з них. Перша модель переважає у Франції та Італії, друга – у США, третя – у ФРН. Останнім часом відбувається поступовий перехід до третьої моделі, яка стане панівною в західних країнах. Порівняно із Західною Європою, в Україні не відбулося моральної реабілітації багатства, що вплинуло на мотивацію благодійності. Прикметно, що в останнє десятиліття, особливо в європейських країнах, створені державні та державно-соціальні фонди, які фінансуються за рахунок бюджетних коштів та внесків меценатів. Загалом, аналізуючи різні форми меценатства та спонсорства у сфері культури країн європейського регіону, можна стверджувати, що в сучасних західних країнах спостерігається широка тенденція до зменшення прямої державної підтримки культури за рахунок непрямої. Залучення коштів підприємців та неурядових організацій у різних формах цілеспрямовано стимулюється державною культурною політикою, законами про меценатство. В Україні втручання держави у благодійну сферу мінімальне. Вона обмежується законодавчим регулюванням благодійної діяльності, реєстрації та обліку благодійних організацій. Водночас певної специфічної нормалізації меценатства та спонсорства немає, оскільки серед інших благодійних заходів вона виділяється переважно меценатами, спонсорами та засобами масової інформації.
Antoshyna I. Models of administrative and legal regulation of sponsorship and patronage in the EU / I. Antoshyna, A. Bondarenko // Baltic Journal of Economic Studies. - Vol. 5. - Issue 5. - Baltija Publishing, 2019. - Р. 18-27.
Keywords: sponsorship; administration model; legal regulation; private fund; art market; social development; спонсорство; модель адміністрування; правове регулювання; приватний фонд; арт-ринок; соціальний розвиток; Research Subject Categories::LAW/JURISPRUDENCE